Residue-based pharmacophore approaches to study protein–protein interactions. (April 2021) - Shrestha, Rojan; Fajardo, Jorge Eduardo; Fiser, Andras
Highlights: Structures are available for most known proteins. Protein-based drugs are discovered at high rates. Structure based pharmacophore approaches can be implemented for protein ligands. MD snapshots based pharmacophores can consider structural flexibility and solvent effect. Abstract : This review focuses on pharmacophore approaches in researching protein interfaces that bind protein ligands. Pharmacophore descriptions of binding interfaces that employ molecular dynamics simulation can account for effects of solvation and conformational flexibility. In addition, these calculations provide an approximation to entropic considerations and as such, a better approximation of the free energy of binding. Residue-based pharmacophore approaches can facilitate a variety of drug discovery tasks such as the identification of receptor–ligand partners, identifying their binding poses, designing protein interfaces for selectivity, or defining a reduced mutational combinatorial exploration for subsequent experimental engineering techniques by orders of magnitudes.